What do coaches think about psychological skills training in soccer? A study with coaches of elite Portuguese teams - de Freitas, S.; Dias, C.; Fonseca, A. (International Journal of Sports Science, 2013)
It is widely recognized that the coach is a key element in the Psychological Skills Training (PST) process. However PST research targeting coaches is very limited, specifically in a soccer context. Therefore, thirteen elite coaches from Portuguese Premier Soccer League were interviewed to explore their thinking about PST process. It was also our aim to examine the coaches` educational background in sport psychology, as well as their opinions about the role of sport psychologists in soccer. Content analysis of the data revealed that participants acknowledge the importance of PST and the role of the sport psychologist in elite soccer. Nevertheless, participants seem to be unprepared to implement and conduct PST programs. A list of barriers to PST interventions in soccer also emerged from the data. Findings provide several applied implications for practitioners (coaches, directors and sport psychologists). They also serve as a guide to future research and contribute to the development of more specific and effective PST interventions with soccer players and coaches.